The Role of Ultrasound in Diagnosing Thyroid Lumps in Asymptomatic Women Aged 18–57 Years in Aljumail City, Libya - Hanan Nasib (المجلة الليبية للدراسات الأكاديمية المعاصرة, 2025)
Background: Thyroid nodules are a prevalent clinical finding, especially among women, with many cases being asymptomatic. The widespread use of high-resolution ultrasound has significantly improved the ability to detect and characterize these nodules, aiding in distinguishing benign from malignant lesions. Features such as calcifications, irregular margins, and the presence of cystic components are critical indicators used in assessing malignancy risk. Classification systems like TIRADS have further enhanced diagnostic accuracy, while fine needle aspiration (FNA) remains a key tool in confirming suspicious cases. Objectives: This study aimed to determine the prevalence of thyroid nodules in asymptomatic women aged 18–57 years in Aljumail City, Libya, and to evaluate the diagnostic effectiveness of ultrasound, particularly in identifying ultrasound features associated with malignancy. Methods: A cross-sectional ultrasound examination was performed on 157 asymptomatic women. Nodules and cysts were identified and classified based on their sonographic characteristics. Features suggestive of malignancy—such as calcifications and irregular margins—were recorded. The TIRADS classification system was used to stratify risk, and fine needle aspiration biopsy was recommended for nodules with suspicious features. Results: The study found that 41% of the women had detectable thyroid abnormalities. Of these, 67.2% were cysts and 32.8% were solid nodules. There was a statistically significant association between suspected malignancy and the presence of calcifications (p = 0.008) as well as irregular margins (p < 0.001). These findings emphasize the importance of routine ultrasound screening and risk stratification for early detection and appropriate management of thyroid cancer.